1991
DOI: 10.1136/bjo.75.11.649
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double-blind trial of bromovinyldeoxyuridine (BVDU) and trifluorothymidine (TFT) in dendritic corneal ulceration.

Abstract: The results of a randomised double-blind clinical trial of 0.1% bromovinyldeoxyuridine (BVDU) and 1% trifluorothymidine (TFT) in 60 patients with corneal dendritic ulceration are presented. There was no significant difference between BVDU and TFT in terms of numbers of ulcers healed (p=0-61), mean healing time (p=0065), and cumulative healing rate (p=0058). No serious side effects were observed, though transient stinging was recorded in five patients receiving TFT and in three patients receiving BVDU. One pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…The clinical course of HSV epithelial kerat itis in our patients was comparable to those of series treated with modern antivirals alone [2,3], considering that some cases were excluded as treatment failures in the latter study [3], Thus, there was no obviously evident effect on the disease. Nevertheless, the indication that in 3 patients the course of the present episode was apparently shorter than previous ones had been may deserve further attention.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The clinical course of HSV epithelial kerat itis in our patients was comparable to those of series treated with modern antivirals alone [2,3], considering that some cases were excluded as treatment failures in the latter study [3], Thus, there was no obviously evident effect on the disease. Nevertheless, the indication that in 3 patients the course of the present episode was apparently shorter than previous ones had been may deserve further attention.…”
Section: Discussionsupporting
confidence: 51%
“…Herpes simplex virus (HSV) keratitis re mains a therapeutical challenge, despite a wide array of useful or potentially useful treat ments, including antiviral drugs, such as triflu orothymidine (TFT), acyclovir or bromovinyldeoxyuridine, interferon and debridement [1][2][3]. One treatment modality for HSV kerat itis that has periodically reappeared in the lit erature over the last three decades is the top ical application of immunoglobulins (Ig) [4][5][6][7], The preparations were instilled into the eye or injected subconjunctivally.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence that a topical antiviral might also affect future episodes of epithelial keratitis is conflicting. Several studies included in this systematic review found no differential effect between interventions on later recurrences (HEDS Group 1997; McGill 1981; Patterson 1963a; Power 1991; Wilhelmus 1981a; Yamagami 1998). On the other hand, several included studies comparing ganciclovir and acyclovir observed that topical ganciclovir reduced the risk of ocular recurrence during the year after completing treatment (Han 2010; Lin 2011; Lin 2014; Liu 2012a; Liu 2012b; Liu 2014a; Wang 2014a; Yang 2008; Zhen 2012).…”
Section: Discussionmentioning
confidence: 86%
“… 1 Included idoxuridine studies: Altinisik 1987; Blake 1977; Colin 1981; Collum 1980; Kitano 1985; Klauber 1982; Laibson 1977; MacKenzie 1964; Markham 1977; McCulley 1982; Panda 1995; Pavan-Langston 1976; Vannini 1986; Wellings 1972 2 Included vidarabine studies: Blake 1977; Collum 1985; Coster 1976; Coster 1979; Denis 1983; Jackson 1984; Markham 1977; Pavan-Langston 1976; Pavan-Langston 1981; van Bijsterveld 1980; Yeakley 1981; Young 1982 3 Included trifluridine studies: Behrens-Baumann 1992; Coster 1976; Coster 1979; Hoang-Xuan 1984; Panda 1995; Parlato 1985; Power 1991; van Bijsterveld 1980; Wellings 1972 (omitting La Lau 1982 because of imprecise assessment) 4 Included acyclovir studies: Altinisik 1987; Carmassi 1993; Colin 1981; Colin 1983; Colin 1984; Colin 1987; Colin 1997a; Colin 1997b; Colin 2007b; Collum 1980; Collum 1985; Collum 1986; Denis 1983; Hoang-Xuan 1984; Huang 2008a; Jackson 1984; Jensen 1982; Kitano 1985; Klauber 1982; McCulley 1982; Panda 1995; Pavan-Langston 1981; Wilhelmus 1981a; Yeakley 1981; Young 1982 (omitting La Lau 1982 because of imprecise assessment) 5 Included brivudine studies: Panda 1995; Power 1991; van Bijsterveld 1989 6 Included ganciclovir studies: Colin 1997a; Colin 1997b; …”
Section: Figurementioning
confidence: 99%
“…Trifluridine, a fluorinated pyrimidine nucleoside, acts as a thymidine analog. It has better or equal efficacy compared to older topical agents [10]. Trifluridine is activated by viral and host cell thymidine kinase and is integrated into the DNA of both the herpes virus and host cells.…”
Section: Hsv Epithelial Keratitismentioning
confidence: 99%